Anatomy and Histology Study of Sinoatrial Node in Mammals’ Heart - Farahmand, Mohammad Yosuf (Journal of Natural Sciences – Kabul University, 2022)
The heart's conductivity system comprises nodes and fibers, with the sinoatrial node recognized as the pacemaker. This node initiates action potentials that propagate throughout the heart, leading to cardiac myocyte contraction, which pumps blood into the circulatory system to deliver oxygen and nutrients to body cells. The anatomical location of the sinoatrial node varies among mammals, and histological differences such as cellular structure, node artery, collagen framework, nerve fiber regulation, and glycogen content are also observed. This article aims to describe the anatomical and histological characteristics of the sinoatrial node.